Fungal Fermented Protein (FFP) : Alternative Ingredient to be Used in Muscovy Duck Diets - Usaneeporn Soipeth; Saowanit Tongpim; Vichai Leelavatcharamas; Terdsak Khammeng (Turkish Journal of Agriculture: Food Science and Technology)
Fungal fermented protein (FFP) was the alternative feedstuff from Aspergillus niger and can be an interesting choice in poultry diets because these product was containing 20.49 % of crude protein and high leucine (0.58 %), phenylalanine (0.58 %) and lysine (0.38 %) and contained no aflatoxin. The experiments were performed using a completely randomized design with 6 treatments and 3 replications employing eight 1-day-old, mixed sex muscovy ducks (Cairina moschata) per experimental unit. The control birds were fed with a basal diet whereas the test birds were fed with FFP at 5, 10, 15, 20 and 25 % of diet. Feed and water were provided ad libitum. The feed intake of the starter showed no significant difference while the grower and finisher had higher feed intake with higher levels of FFP. In contrast, the high level of FFP yielded the lower final body weight and body weight gain, resulting in the high feed conversion ratio (4.38). For the performance of overall period, the ducks fed with 20 % FFP had higher average daily gain (29.40 g/b/d), body weight gain (2,471 g/b) and feed conversion ratio (3.63). No deaths were found in any pens and the ducks remained in good health.